2015
DOI: 10.1039/c4gc01470g
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of novel halogen-free Brønsted–Lewis acidic ionic liquid catalysts and their applications for synthesis of methyl caprylate

Abstract: Eco-friendly [HSO3-pmim]+(1/2Zn2+)SO42− ionic liquid catalysts facilitates synergistic Brønsted and Lewis acidity for esterification of n-caprylic acid to methyl caprylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 46 publications
3
29
0
1
Order By: Relevance
“…Upon withdrawing the products in the upper layer, the precipitated catalyst could then be recycled after simple filtering and washing treatments. Similar behaviors were also found in other HPA-IL systems [29,37,43].…”
Section: Esterification Reactionsupporting
confidence: 78%
See 2 more Smart Citations
“…Upon withdrawing the products in the upper layer, the precipitated catalyst could then be recycled after simple filtering and washing treatments. Similar behaviors were also found in other HPA-IL systems [29,37,43].…”
Section: Esterification Reactionsupporting
confidence: 78%
“…S1a of the Supplementary materials, the parent MIM-PS IL showed only a weight-loss peak centering at ca. 642 K[36,37]. Since the [MIM-PSH] x H 4−x PVMo 11 O 40 (x = 1.0−4.0) catalysts exhibit similar thermal properties, hence, similar TGA-DTG profiles were observed.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Conventionally,h omogeneousc atalysts, such as H 2 SO 4 ,H Cl, H 3 PO 4 , p-toluenesulfonic acid, or acidic ionicl iquids, are commonly exploited for esterification reactions. [8,9] However,t he applicationsoft hese mineral acids are hampered by severe environmental and recovery cost issues. Their inherents hortcomings include their highly corrosive, toxic, non-dissociable, intricate separation and purification, making recovery/reuse rather impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their remarkable capacity to delignify and solubilize cellulose, the ILs are often used for pretreating lignocellulosic biomass before hydrolysis [10][11][12][13][14][15]. On the other hand, Davis et al reported acidic ILs having an acidic group such as a sulfo group in their cationic and/or anionic structures [16][17][18][19][20], and the acidic ILs exhibit higher catalytic activity in cellulose hydrolysis compared to sulfuric acid [21].…”
Section: Introductionmentioning
confidence: 99%